Establishing Quality Standards for Applied Behavior Analytic Skill- Acquisition Interventions: a Translational Model with Undergraduate Students - (:unkn) unknown (My University, 2018)
Treatment integrity is the extent to which components of an intervention are implemented as intended (Gresham, 1989). Recent behavior-analytic literature has begun to evaluate the effects of impaired treatment integrity on efficacy and efficiency of skill-acquisition interventions. We extended current literature on the effects of errors of omission and commission of reinforcement on the acquisition of conditional discriminations. We used a translational research model to replicate and extend Hirst and DiGennaro Reed (2015) to investigate the effects of impaired treatment integrity with undergraduate students. We compared the efficacy and efficiency of instruction implemented with varying degrees of integrity in a parametric analysis using a randomized-control group design. We used a computer program, which erred on 0% to 50% of trials, to approximate procedures used to teach conditional discriminations in behavior analytic skill-acquisition interventions. The purpose was to identify a level of error at which most participants could still acquire the task. Greater than 80% of participants assigned to integrity levels at or above 85% acquired the skill; therefore, errors of reinforcement occurring on 15% or fewer trials did not hinder or slow acquisition for most participants. These results could inform future research with children diagnosed with autism spectrum disorder.
Keywords: applied behavior analysis; efficacy; efficiency; errors of commission; errors of omission; treatment integrity